2017
DOI: 10.1134/s0040577917010111
|View full text |Cite
|
Sign up to set email alerts
|

Deformed Hořava–Lifshitz cosmology and stability of the Einstein static universe

Abstract: Stability of the Einstein static universe versus the linear scalar, vector and tensor perturbations is investigated in the context of deformed Hořava-Lifshitz cosmology inspired by entropic force scenario. A general stability condition against the linear scalar perturbations is obtained. Using this general condition, it is shown that there is no stable Einstein static universe for the case of flat universe, k = 0. For the the special case of large values of running parameter of HL gravity ω, in a positively cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…In GR, this was reconsidered, and it was found that the Einstein static universe can be stable against small inhomogeneous vector and tensor perturbations as well as adiabatic scalar density perturbations if the universe contains a perfect fluid with w = c 2 s > 1/5 [25,26,31]. Of course, the stability of the Einstein static universe has also been extensively studied in many modified gravities, for example, loop quantum cosmology [32], f (R) theory [33][34][35], f (T ) theory [36,37], modified Gauss-Bonnet gravity [38,39], Brans-Dicke theory [40][41][42][43], Horava-Lifshitz theory [44][45][46], massive gravity [47,48], braneworld scenario [49][50][51], Einstein-Cartan theory [52], f (R, T ) gravity [53], hybrid metric-Palatini gravity [54] and so on [55][56][57][58][59][60][61][62]. We refer to e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In GR, this was reconsidered, and it was found that the Einstein static universe can be stable against small inhomogeneous vector and tensor perturbations as well as adiabatic scalar density perturbations if the universe contains a perfect fluid with w = c 2 s > 1/5 [25,26,31]. Of course, the stability of the Einstein static universe has also been extensively studied in many modified gravities, for example, loop quantum cosmology [32], f (R) theory [33][34][35], f (T ) theory [36,37], modified Gauss-Bonnet gravity [38,39], Brans-Dicke theory [40][41][42][43], Horava-Lifshitz theory [44][45][46], massive gravity [47,48], braneworld scenario [49][50][51], Einstein-Cartan theory [52], f (R, T ) gravity [53], hybrid metric-Palatini gravity [54] and so on [55][56][57][58][59][60][61][62]. We refer to e.g.…”
Section: Introductionmentioning
confidence: 99%